Evaluation of parametric and non-parametric methods for power curve modelling of wind turbines - Panahi, Delshad; Deilami, Sara; Masoum, Mohammad Sherkat (2016)
The growing applications of wind power systems and their essential roles in renewable energy production require development of accurate methods for their parameter identification such as the wind turbine power curves. This paper evaluates and compares the parametric and non-parametric approaches for power curve modelling of wind turbine which is a very complicated and nonlinear function of different mechanical, electrical and metrological input parameters. In fact achieving a complete model that can accurately describe the turbine output characteristic is very difficult. However, there are different modelling techniques that could lead to have a better estimation of turbine generation model. In this paper, four different algorithms for modelling the output power of wind turbines in form of two strategies using two case studies will be developed and the results of different models will be compared. © 2015 Chamber of Electrical Engineers of Turkey.